Do Mutual Funds Have Decreasing Returns to Scale? Evidence from Fund Mergers - McLemore, Ping (Journal of Financial and Quantitative Analysis, 2019)
Using mergers as shocks to fund size, I analyze the return-to-scale property of mutual funds. I find that acquiring funds’ performance deteriorates after experiencing a positive shock in size resulting from mergers, and liquidity plays an important role in the negative relationship between size and performance. I also find that the decline in performance is not due to higher performance prior to the merger, nor driven by higher integration costs after the event. These findings are consistent with mutual funds having decreasing returns to scale and thus provide empirical evidence that supports the theoretical model of Berk and Green (2004).